The example of hypocrisy of the state - Erdoğan, Ali (My University, 2019)
The fact that the applicant, who was 14 years old, was left alone at home due to the arrest of the newcomer family as a result of the incident in Bulgaria was remarkable. The ECHR and the domestic courts did not support the attitudes of law enforcement officers representing the state and found human rights violations there. According to the way the mother shook her head at the court and gave a statement through an interpreter, the court did not make a decision of violation for the period after 6 December by changing it’s opinion.

Bulgaristanda gerçekleşen olay neticesinde yeni gelen ailenin tutuklanması sebebiyle 14 yaşında olan başvurucunun evde tek başına bırakılması dikkat çekici unsurdur. AİHM ve yerel mahkemeler devleti temsil eden kolluk kuvvetlerinin tavırlarını desteklemez ve burada insan hakları ihlali bulurken, mahkemede tercüman vasıtasıyla ifade veren annenin başını sallama şekline göre görüşünü değiştirerek 6 Aralık sonrası dönem için ihlal kararı verilmemiştir.
The obligation of the state about protection to minors in the light of the case of hadzhieva V. Bulgaria1
Keywords: Çocuk İhmali; Küçüklerin Korunması; Yeni Gelenler; Tercüman; Devletin Yükümlülüğü; Child Neglect; Protection to Minors; Newcomers; Interpreter; Obligation of the State